SUSTAINABILITY AND GENDER IMPLICATION OF TEA HARVEST MECHANIZATION IN WEST JAVA - Kralawi Sita; Erna Herawati; Silvia Senjaya; Yulianingsih Yulianingsih (Universitas Padjadjaran, 2023)
Indonesian tea industry has applied harvest mechanization to improve harvest productivity and profit due to a labor shortage. In order to maintain the sustainability of this mechanization, it is crucial to assess the balance of economic, environment, and social impact of the mechanization. This study aims at exploring the sustainability of mechanization in three tea industries in Indonesia using sustainability intensification (SI) indicators framework. Drawing on the case of three tea plantations industry in the West Java, this study applied a descriptive exploratory qualitative method. Data were collected through participant observation, in depth interviews, and focus group discussions. Data were analyzed using five domains of sustainability intensification (SI) indicators, namely productivity, economic, environment, human, and social domain. Findings of this study suggest that tea harvest mechanization increases productivity and economic profit, although the usage of fuel to operate the machine has contributed to the air pollution in the plantation area. Tea harvest mechanization also improve human domain by increasing workers household income. In social domain, it strengthens social capital among workers and promotes the formation of a new gender division of labor which is more inclusive. In order to enhance sustainability of mechanization in Indonesian tea industry, it is crucial to re-design the technology into a more gender friendly, increase women's capacity and access to resources, re-assure gender balance and equity in group work, and strengthen sustainable Occupational Health, and Safety (OHS) programs.